Ginsenoside Rg3 for Chemotherapy-Induced Myelosuppression: A Meta-Analysis and Systematic Review - Pan, Linlin; Zhang, Tingting; Cao, Hongfu; Sun, Haiyang; Liu, Guirong (Frontiers in Pharmacology, 2020)
Patients with advanced cancer often undergo myelosuppression after receiving chemotherapy. However, severe myelosuppression results in treatment delay, and some can even be life-threatening. At present, cancer patients undergoing chemotherapy urgently need effective intervention strategies to prevent myelosuppression. Fortunately, ginsenoside Rg3 has shown promise as an anti-myelosuppression agent. Therefore, this study was conducted to evaluate the effectiveness of ginsenoside Rg3 in preventing chemotherapy-induced myelosuppression in cancer patients. The PubMed, Cochrane Library, EMBASE, China National Knowledge Infrastructure (CNKI), Weipu (VIP) and Wanfang databases were searched in this study. A total of eighteen trials which reported on 2,222 subjects were identified. All trials concerning the use of ginsenoside Rg3 for the prevention of chemotherapy-induced myelosuppression (the decline of leukocyte, hemoglobin, platelet and neutrophil counts) were randomized controlled trials. Dichotomous data were expressed as Odds Ratio (OR) with their respective 95% confidence intervals (CI). The Cochrane evidence-based medicine systematic evaluation was used to evaluate the methodological quality of the included trials. The Review Manager 5.3 and Stata 12.0 software were used to perform the statistical analyses. The trial sequential analysis (TSA) was used to evaluate information size and prevention benefits. The results revealed obvious ginsenoside Rg3-induced improvement in the leukocyte (OR 0.46, 95% CI 0.37 to 0.55), hemoglobin (OR 0.64, 95% CI 0.53 to 0.77), platelet (OR 0.60, 95% CI 0.48 to 0.75) and neutrophil (OR 0.62, 95% CI 0.43 to 0.90) counts at toxic grades I-IV, and leukocyte (OR 0.39, 95% CI 0.28 to 0.54) counts at toxic grades III-IV. The sensitivity analysis revealed that the results were robust. The Egger’s test indicated that there was no publication bias in the results. Overall, this study suggested that ginsenoside Rg3 is beneficial for alleviating the chemotherapy-induced decrease in leukocyte, hemoglobin, platelet and neutrophil counts. However, the confirmation of the ginsenoside Rg3 can be recommended for myelosuppression patients was limited due to poor methodological quality. Thus, more rigorously designed RCTs are required to assess the efficacy of ginsenoside Rg3 for myelosuppression.